Transgenic Rescue of Spermatogenesis in Males With Mgat1 Deleted in Germ Cells - Biswas, Barnali; Batista, Frank; Akintayo, Ayodele; Aguilan, Jennifer; Stanley, Pamela (Frontiers in Cell and Developmental Biology, 2020)
MGAT1 and complex N-glycans are required for spermatogenesis and fertility. Conditional deletion of Mgat1 in spermatogonia (Mgat1 cKO) causes reduced ERK1/2 signaling and the formation of multinucleated germ cells (MNC). Here we show that glycomics analysis of N-glycans released from fixed testis sections and analyzed by MALDI imaging mass spectrometry (MALDI-IMS) revealed a loss of MGAT1 activity in all germ cells based on the accumulation of the oligomannosyl substrate of MGAT1. To determine in which type of germ cell MGAT1 is essential for spermatogenesis, we generated Mgat1 cKO males that also expressed a Mgat1-HA transgene under the control of a germ cell-specific promoter - Stra8 for spermatogonia, Ldhc for spermatocytes and Prm1 for spermatids. Males expressing each Mgat1-HA transgene were fertile, and both males and females transmitted each transgene. When Stra8-Mgat1-HA was expressed in Mgat1 cKO males, spermatogenesis was rescued based on the morphology of testis sections, the complement of N-glycans on basigin, lectin histochemistry, MALDI-IMS and fertility. By contrast, neither Ldhc-Mgat1-HA expressed in spermatocytes, nor the Prm1-Mgat1-HA transgene expressed in spermatids rescued spermatogenesis or fertility in Mgat1 cKO males. Therefore, MGAT1 must be expressed in spermatogonia for spermatogenesis to proceed normally.